PENDAMPINGAN MILENIAL HOBI ZAKAT MELALUI PENGAPLIKASIAN ZAKAT DIGITAL BAGI REMAJA MASJID - Subardin, Muhammad; Imelda, Imelda; Andaiyani, Sri (SELAPARANG Jurnal Pengabdian Masyarakat Berkemajuan, 2021)
ABSTRAKKegiatan pengabdian kepada masyarakat (PKM) ini memiliki tujuan untuk memberikan pemahaman mengenai zakat dan manfaat teknologi komunikasi guna mengaplikasikan zakat. Tim Pengabdian Fakultas Ekonomi UNSRI telah melaksanakan pendampingan kepada generasi milenial yang hobi zakat. Pelaksanaan kegiatan berlangsung 1 hari pada Jumat, 15 November 2019. Peserta terdiri dari 30 Remaja Mushola Ukhuwah Fakultas Ekonomi. Metode pelaksanaan kegiatan berupa memberikan ceramah dan tutorial. Tim PKM menyampaikan edukasi berkenaan dengan zakat, manfaat zakat  dan jenis zakat. Peserta pendampingan diberikan tutorial penggunaan zakat digitial dan dapat menghitung zakat dengan aplikasi kitabisa.com. Untuk mengevaluasi kegiatan PKM, peserta pemdampingan diminta untuk mengisi kuisioner yang terkait dengan pemahaman materi. Berdasarkan hasil kuesioner, pendampingan zakat yang telah dilaksanakan menunjukkan pemahaman peserta yang telah mencapai 71%. Capaian ini diharapkan dapat meningkatkan penggunaan zakat digital sebagai metode pembayaran zakat bagi generasi millennial. Kata kunci : zakat; milenial; zakat digital. ABSTRACTThe community service activity (PKM) aims to provide an understanding of zakat and the benefits of communication technology to apply zakat. The team of Faculty of Economics UNSRI has provided assistance to the millennial generation who like zakat. The activity was carried out for 1 day on Friday, November 15, 2019. The participants consisted of 30 Youths of the Ukhuwah Mosque, Faculty of Economics. The method of carrying out activities is in the form of giving lectures and tutorials. The PKM team delivered education regarding zakat, the benefits of zakat and the types of zakat. Mentoring participants are given tutorials on the use of digital zakat and can calculate zakat with the kitabisa.com application. To evaluate PKM activities, mentoring participants were asked to fill out a questionnaire related to understanding the material. Based on the results of the questionnaire, the zakat assistance that has been implemented shows the participants' understanding which has reached 71%. This achievement is expected to increase the use of digital zakat as a method of paying zakat for the millennial generation. Keywords : zakat; millennial; digital zakat.